Evaluation of Reliability of Rupture and Expected Value of Fracture Speed of Ceramic Turbine Wheel Taking the Effect of Residual Stresses - Jasim, Haider Hadi (Nahrain University College of Engineering Journal, 2010)
In this paper, Weibull uni-axial and multiaxial distribution function including residual stresses is developed and applied to evaluate the reliability of fracture and expected value of fracture rotating speed of turbine rotor wheel having blades manufactured from ceramic material and have inner crack. The residual stress is measured by X-Ray method. Third cases are considered, first taking only the effect of rotational loading (radial and tangential stresses) in ceramic disc, secondtaking the effect of rotational and thermal stresses in ceramic disc, and third taking the effect of rotational and thermal stresses in ceramic blade. As a result, there is a convergence between results gets from uniaxial and multi-axial distribution function, and the residual stresses will reduce the risk of fracture of wheel and blade. The expected values of rupture strength of ceramic blade is higher than of that of disc material, therefore the failure occurs in blade first than in discmaterial in service survivaL